The Relationship Between Self-Efficacy and Adversity Quotient and Academic Stress Among 12th-Grade Students at High School X in Bandung - Ananda Salma Aisyatul Mardiah; Pratidina Ekanesia; Rifqi Farisan Akbar (International Journal of Marketing & Human Resource Research, 2026)
Senior high school students, specifically those in the final year of high school cramming for National Selection Based on Achievement and Academic Aptitude Test, sometimes suffer from academic stress as a result of the heavy intellectual burden they are required to carry. This study aims “to analyze the influence of self-efficacy and adversity quotient on academic stress among 12th-grade students at High School X in Bandung.” The researchers in this study used a multiple correlation design and a quantitative technique. From a total of 360 pupils, 78 were chosen utilizing a purposive sampling method. The researchers used a Likert-scale questionnaire to measure Self-efficacy, Adversity Quotient, and academic stress. Data analysis was performed using classical assumption tests, multiple linear regression, Pearson Product-Moment correlation tests, and the coefficient of determination. The results showed that “self-efficacy had a negative and significant effect on academic stress.” This means that the higher students’ self-efficacy, the lower the level of academic stress they experience. Meanwhile, “Adversity Quotient did not show a significant effect on academic stress when analyzed individually.” However, “Self-efficacy and Adversity Quotient together had a significant effect on academic stress”, contributing 30.4%, while other variables that were not considered in this study accounted for the rest. According to these results, self-efficacy is more important than the adversity quotient for lowering academic stress. Therefore, building students’ self-confidence and psychological resilience should be a priority in efforts to reduce academic stress in the school environment.